Diversity in electronic structure and vibrational properties of fullerene isomers correlates with cage curvature. (April 2016) - Witek, Henryk A.; Irle, Stephan
Abstract: A theoretical study of pentagon/hexagon-bearing isomers of the C32 and C86 fullerenes suggests that the diversity in electronic structure and vibrational properties is determined by the surface curvature of the fullerene cage rather than by the global bond network topology. The latter plays a greater role in small, highly constrained fullerene cages, while it can be safely ignored in the case of larger isomers. Selection rules of infrared and Raman spectroscopy are the origin for exceptions from this pattern for bond topologies corresponding to high point-group symmetries of the fullerene cage. The presented data conforms to the common knowledge that discriminating between various isomers of larger fullerenes can constitute a difficult experimental task.